Relevansi Nilai-Nilai Peradaban Islam Klasik dalam Perkembangan Dunia Modern - Anita Pronika (Multiverse: Open Multidisciplinary Journal, 2025)
The classical Islamic civilization, particularly during the Abbasid and Andalusian periods (750–1258 CE), played a pivotal role in shaping intellectual, socio-political, economic, educational, and cultural developments that influenced both the Islamic world and broader human civilization. Amid contemporary challenges marked by globalization, secularization, and the distortion of Islamic values by extremist interpretations, this study investigates the relevance of classical Islamic civilizational values in addressing the ethical and structural crises of the modern world. Employing a qualitative descriptive approach through an extensive library-based analysis of classical and contemporary sources, the research examines how foundational principles such as social justice, interreligious tolerance, ethical scholarship, accountable leadership, and spiritually grounded education can be systematically recontextualized. The findings reveal that these values are not merely historically significant but remain conceptually compatible and normatively applicable to modern contexts, particularly in education, governance, economic systems, and interfaith relations. The study argues that the deliberate reintegration of these core principles can contribute to a more ethical, sustainable, and intellectually balanced contemporary civilization capable of responding to moral, social, and epistemic disruptions generated by extreme secularization and global transformation.